2017
DOI: 10.1186/s12929-017-0366-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent redox status in the brain stem of NO-deficient hypertensive rats

Abstract: BackgroundThe brain stem contains important nuclei that control cardiovascular function via the sympathetic nervous system (SNS), which is strongly influenced by nitric oxide. Its biological activity is also largely determined by oxygen free radicals. Despite many experimental studies, the role of AT1R-NAD(P)H oxidase-superoxide pathway in NO-deficiency is not yet sufficiently clarified. We determined changes in free radical signaling and antioxidant and detoxification response in the brain stem of young and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 104 publications
1
16
2
1
Order By: Relevance
“…Many studies have observed that chronic inhibition of NOS induced with L-NAME successfully decreases the activity of NOS in major systems involved in the regulation of blood pressure, such as the brain, vessels, heart, or kidney, in normotensive and hypertensive rats [21, 42, 43]. However, we did not observe this inhibitory effect in the kidneys of Wistar rats.…”
Section: Discussioncontrasting
confidence: 91%
See 4 more Smart Citations
“…Many studies have observed that chronic inhibition of NOS induced with L-NAME successfully decreases the activity of NOS in major systems involved in the regulation of blood pressure, such as the brain, vessels, heart, or kidney, in normotensive and hypertensive rats [21, 42, 43]. However, we did not observe this inhibitory effect in the kidneys of Wistar rats.…”
Section: Discussioncontrasting
confidence: 91%
“…Administration of L-NAME to young SHRs involves kidney damage, and it is often used as a model for studying chronic kidney diseases typically observed in patients with essential hypertension [27]. Used doses of the inhibitors were adjusted based on previous experiences from our laboratory as well as observations of other experimental works [21, 28, 29]. Experimental studies have observed that higher doses of 7-NI result in nonspecific inhibition of NOS and the inhibition of eNOS has also been observed [30].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations